Vitamin D status in 5-15 years old children attending pediatric OPD in tertiary care hospital in Jammu and Kashmir, North India: a cross sectional study - Chowdhary, Sumaira; Shafi, Mudasir; Nazir, Heena (International Journal Of Community Medicine And Public Health, 2023)
Background: Vitamin D is vital in children mainly because of its profound effect on growth, development, immune system and importantly bone health. Recent evidence suggests maintaining 25 (OH) D levels above 20 ng/ml for maximizing health benefits. Objectives were to assess the vitamin D status in children in the age group of 5-15 years attending a tertiary care teaching institute of North India and to analyze the factors which can contribute to vitamin D deficiency in these children. Methods: It was a cross-sectional study. 5-15 years old children attending the outpatient department were included in the study. Children with co morbid conditions that affect vitamin D metabolism and those children on chronic drug treatment and on vitamin D supplementation were excluded from the study. Results: Average age of study population was 8.93±2.02. In the study 170 (18.47%) children among a total of 920 had a normal vitamin D status while the rest 750 children (81.52%) had insufficient vitamin D status (25 hydroxy vitamin D <30 ng/ml). Among these children 190 (26.38%) had suboptimal vitamin D levels, 300 (40%) were deficient, 143 (19.06%) had severe and 117 (15.6%) had very severe deficiency of vitamin D. The average vitamin D level among the study population was 12.33±11.13 ng/ml. There was significant statistical association between vitamin D deficiency and stunting (p=0.003). No statistically significant association was found between outdoor activity. Conclusions: Vitamin D insufficiency was documented in 81.52% of 5-15 years old children and there was a significant association between stunting and vitamin D deficiency.